Digital Legal Transformation: Legal Strategies for Strengthening National Cybersecurity - Ferry Irawan Febriansyah; Afiful Ikhwan; Ulya Shafa Firdausi; Ayub Dwi Anggoro (NAJAHA, 2026)
Digital legal transformation in Indonesia has become imperative in response to the increasingly complex and transnational nature of cybercrime. Rapid technological development has expanded opportunities for criminal activities by exploiting regulatory gaps and weaknesses in digital security systems, thereby challenging the effectiveness of existing legal frameworks. This situation demands a legal system that is adaptive, responsive, and capable of safeguarding national cybersecurity while protecting digital human rights. The objective of this study is to analyze the transformation of Indonesia’s digital legal framework in addressing cybercrime and to assess its alignment with international legal instruments. This research particularly focuses on the adequacy of regulatory arrangements and the effectiveness of institutional coordination in responding to cyber threats. This study employs a normative legal research method by examining statutory regulations related to cybercrime, with particular attention to the Electronic Information and Transactions Law (UU ITE), as well as relevant international conventions and legal standards. Legal materials are analyzed systematically to evaluate the coherence of regulations and the operationalization of Indonesia’s cybercrime response model. The findings indicate that Indonesia’s digital legal transformation is carried out through structured efforts rather than merely producing regulatory impacts. In the short term, these efforts focus on strengthening regulations, enhancing law enforcement capacity, improving digital forensic infrastructure, and standardizing digital evidence handling. In the long term, transformation emphasizes institutional integration, regulatory harmonization, and international cooperation to address transnational cybercrime. This study is original in conceptualizing digital legal transformation as a phased legal–institutional strategy. However, its normative approach limits empirical assessment of implementation effectiveness.